Water and urban space: Some theoretical considerations on the relationship between city and river - Santasusagna Riu, Albert; Tort Donada, Joan (Documents d'Anàlisi Geogràfica, 2019)
This paper proposes an approach to the study of the relationship between the fluvial environment (the river) and the urban space (the city) from a theoretical and conceptual viewpoint. It is based on a reflection that allows a series of terminological nuances considered essential to understand the complexity of the urban-river system. The concepts under analysis have been, for the most part, coined and disseminated by modern geography, but also studied in related fields such as urbanism and architecture. Likewise, these are concepts that have had a particular translation depending on the academic context and tradition. Our contribution focuses on the analysis and systematization of this terminological corpus in order to establish a theoretical basis that allows for a better understanding of the relationship between river and city.